2022
DOI: 10.1111/jcmm.17643
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0000052/miR‐382‐3p axis induces PD‐L1 expression and regulates cell proliferation and immune evasion in head and neck squamous cell carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC), which includes tumours of the lip, oral cavity, larynx, oropharynx and hypopharynx, accounted for 3.9% of new cases and 3.7% of cancer deaths in 2020. In the Asia region, it has been observed to have the highest incidence. 1 Despite multimodal treatment, including surgery and radiotherapy, with or without conventional chemotherapy, around 30%-40% of patients with aggressive disease develop distant metastases within 5 years. 2 Checkpoint blockade immunotherapy has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Circ_0000052 targeted miR-382-3p and attenuated its inhibition of PD-L1 in head and neck squamous cell carcinoma. 36 In the hypoxic microenvironment of hepatocellular carcinoma, circPRDM4 recruited HIF-1α to the PD-L1 promoter region and promoted PD-L1 upregulation. 37 Similarly, we found that circYAP1 increased PD-L1 expression by promoting its transcription in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Circ_0000052 targeted miR-382-3p and attenuated its inhibition of PD-L1 in head and neck squamous cell carcinoma. 36 In the hypoxic microenvironment of hepatocellular carcinoma, circPRDM4 recruited HIF-1α to the PD-L1 promoter region and promoted PD-L1 upregulation. 37 Similarly, we found that circYAP1 increased PD-L1 expression by promoting its transcription in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The study not only confirms that the IFN-γ/JAK2/STAT1 signaling pathway can induce PD-L1 overexpression in HNSCC but also uncovers a novel mechanism by which the upregulated circ_0000052 mediates PD-L1 overexpression. Specifically, circ_0000052 competes with miR-382-3p for binding and alleviates its inhibitory effect on PD-L1 expression ( 156 ).…”
Section: Micrornas: Bridging the Gap Between Gene Regulation Immune C...mentioning
confidence: 99%
“…Its interaction with the ligand PD-L1 (programmed death-ligand 1) on cancer cells prevents the activation of tumor antigen-specific T cells, contributing to the immune evasion of cancer cells 100 , 101 . circ_0000052 upregulates PD-L1 expression by sequestering miR-382-3p, thereby promoting the malignant progression of HNSCC 77 . Ge et al demonstrated that EBV-encoded circBART2.2 expression promotes PD-L1 transcription through the binding of circBART2.2 to the helicase domain of RIG-I and the activation of transcription factors IRF3 and NF-κB, resulting in immune evasion of NPC 102 .…”
Section: Functional Roles and Mechanisms Of Circrna In Hnsccmentioning
confidence: 99%